A conceptual paper on the role of local champion in rural tourism destination in Malaysia - Abas, Siti Aisah; Abd Halim, Norhazliza (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The prosperous of rural tourism development is rely not only on the local community participation but, it is depending on the effectives of leader to navigate the group and the followers to achieve certain objectives. However, there is a little empirical study has been done on this area by the scholars. Thus, this conceptual research undertaking on exploring the roles and characteristics of local champion in rural tourism destination in Malaysia. A review of literatures and documents from the Malaysia Plan, Rural Tourism Master Plan and handbook on the Community-Based Tourism has been presented as source of data collection. This study analyses literature on the emergence concept and roles of local champion particularly in rural tourism destination. Therefore, there is a vital need to study on the role of leadership and concept of local champion in rural tourism in order to sustain the tourism industry.